Polycarpon tetraphyllum (L.) L. (Caryophyllaceae) and Arabis stelleri DC. (Brassicaceae): two new records for the flora of Mainland China - Guican Lin; Ming Chen; Hongyang Zhu; Biyong Ni; Ge Gao; Chengzi Yang; Chang An (Check List)
In recent years, numerous botanical survey projects have been conducted across China, with accurate taxonomic identification being the primary objective of biodiversity research. Within this context, we report the discovery of Polycarpon tetraphyllum (L.) L. (Caryophyllaceae) and Arabis stelleri DC. (Brassicaceae) in Fujian, marking new records for the flora of mainland China. Furthermore, we provide detailed morphological descriptions, color photographs, and comparative taxonomic analyses with related species to scientifically substantiate the records of these two plant species.